Effect of humic acids extracted from different organic sources and inoculation with Bacillus subtilis or Aspergillus Niger on urease activity in calcareous soil - Al-Malaky, Israa AY; Abdulkareem, Mohammed A; Al-Jaberi, Meiad M (Edelweiss Applied Science and Technology, 2024)
Humic substances have received a large share of research and development as amendments to poor fertility soils that are poor in fertility and have deteriorating physical properties, since the process of extracting is a common process and easy to implement, as well as diluting these acids with water enables them to be used at economically acceptable levels over large areas. It is necessary to noticed that the properties of these acids depending on the organic source and the concentration added to the soil. A laboratory experiment was conducted at the Department of Soil Sciences and Water Resources, College of Agriculture, University of Basrah ,IRAQ to demonstrate the effect of humic substances extracted from different sources and inoculation with Bacillus subtilis or Aspergillus niger on the activity of the urease in calcareous soil. Wheat straw, alfalfa leaves, goat waste and poultry waste were composted aerobically for 3 months by filling a hole of 2×2×1.5 m by layers of such waste ,turned weekly for aeration. Each pile was extracted for humic acids (humic acid + fulvic acid) . Humic acid mixed with to soil at levels of 0, 25, and 50 L h-1. The soil was also inoculated with Bacillus subtilis or Aspergillus niger isolated from local soil at rates of 20.06×106 and 40× 103 cfu ml-1, respectively The samples were incubated at field capacity level 28±2°C for 30 days. Urease activity was estimated after 7 or 30 days by determining NH4+ released using steam distillation method . A decrease in urease activity was observed when treated with different types of humic acid compared to the control treatment. The lowest activity was obtained at humic acids extracted from poultry waste, reaching 312.0 and 188.72 µg N-NH4+g-1soil.2h-1 at incubation periods of 7 and 30 days, respectively .The results also indicated that increasing the level of humic acids significantly inhibited the activity of the enzyme. However, in soil treated with Bacillus subtilis or Aspergillus niger, an increase in urease activity was observed compared to the non-inoculation treatment. Treatment with the fungal inoculant had higher activity than the bacterial inoculum, reaching 324.5 and 297.2 µg N-NH4+ g-1 soil 2 hours-1 for both inoculants at a period of 7 days, and 178.09 and 150.31 µg N-NH4+g-1soil.2h-1at a period of 30 days, respectively.It is proposed that the inhibition of urease by humic acid addition may benefit for increasing urea fertilizer efficiency.